Constrained stochastic data sampling for deep learning–based time-lapse hydraulic tomography under reactive-induced permeability evolution - Zi-Yan Chou; Jui-Pin Tsai; Bo-Tsen Wang; Chia-Hao Chang; Ying-Fan Lin; Tian-Chyi Jim Yeh (Journal of Hydrology, 2026)

Interfacial electron redistribution and tandem active sites enable enhanced nitrate to ammonia conversion in Zr-MOF/MoS2 heterostructures - Naveen Karuppusamy; Zi-Yan Zhan; Ruspika Sundaresan; Chun Hsien Wu; Pandiyarajan Anand; Jeyakumar Karthikeyan; Hsu-Feng Lee; Hung-Pin Hsu; Yu-Cheng Shao; Yi-Ping Wang; Ching-Wei Tung (Chemical Engineering Journal, 2026)

Development of magnetic solid-phase extraction with magnetic graphene oxide composite nanospheres for sensitive determination of perfluoroalkyl substances in tea beverages - Xin-Li Song; Tong Sun; Ke-Chao Liao; Hui Lv; Pin-Pin Wang; Dong-Dong Wang; Yan Lu; Lin Li (Analytica Chimica Acta, 2026)

Type I IFNs, IFNc, IFNd1, IFNd2, IFNh, and type II IFNs, IFN-γ and IFN-γrel, and their possible receptors with the identification of two variants of IFNc and IFNh in turbot (Scophthalmus maximus) - Bo Li; Meng Xin Yan; Yu Hang Deng; Xiao Qian Jiao; Shan Nan Chen; Xu Jia Zhang; Jia Le Chen; Xue Yun Peng; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2026)

Assessing the impact of climate variability on exposure indices of Portunid crabs in the Southern East China sea - Irene Chia Ling Lim; Yan-Lun Wu; Wei-Pin Hsu; Muhamad Naimullah; Wei-Yu Lee; Lu-Chi Chen; Kuo-Wei Lan (International Journal of Remote Sensing, 2026)

Optimizing bubble tea packaging sustainability in Taipei: A life cycle assessment and multi-objective optimization approach for circular economy integration - Yan-Ruei Huang; Yu-Kai Liao; Ching-Pin Tung; Wei-Chun Chuang (Resources, Conservation and Recycling, 2026)

Projected impacts of climate change on the spatial distribution and habitat preference of tropical tuna in the Pacific Ocean - Yan-Lun Wu; Ting-Yu Liang; Wei-Pin Hsu; Teruhisa Shimada; Anindya Wirasatriya; Parichat Wetchayont; Chunhua Qiu; Kuo-Wei Lan (Marine Environmental Research, 2026)

Joint inversion of hydraulic and thermal parameter fields using a CNN-based framework and transient hydraulic tomography - Che-Wei Liang; Jui-Pin Tsai; Zi-Yan Chou; Chia-Hao Chang; Bo-Tsen Wang (Journal of Hydrology, 2026)

Multi-target antidiabetic peptides from highland barley (Qingke): Identification, molecular docking, and inhibitory mechanisms against α-amylase, α-glucosidase, and DPP-IV - Juan Li; Muyan Ma; Feng Liang; Yan Du; Wenju Zhou; Pin Ma; Falin Zhang; Zhaoxin Tu; Li Wang; Xinxia Zhang; Ting Li (Food Chemistry, 2026)

Intestinal organoids as advanced modeling platform for food research: a review - Xu Wang; Yanqiu Xia; Jin Wang; Yan Zhang; Pin Lv; Yi Wang (Critical Reviews in Food Science and Nutrition, 2026)

A CPTu-based method for evaluating consolidation characteristics of under-consolidated soils - Yu-cheng Li; Pin-Qiang Mo; Guojun Cai; Zhao Lu; Yan Zhuang; Hai-Sui Yu (Ocean Engineering, 2026)

Active site-rich MIL-101(Fe) derived P-doped iron sulfide/carbon octahedra for oxygen evolution electrocatalysis - Ying-Jun Jhang Jian; Pin-Yan Lee; Subbiramaniyan Kubendhiran; Lu-Yin Lin; Kevin C.-W. Wu; Kuo-Chuan Ho (Journal of Environmental Chemical Engineering, 2026)

Effects of Shifts in Bacterial Community on Improving Water Quality and Growth Performance of Pacific Whiteleg Shrimp (Litopenaeus vannamei) in Biofloc Systems - Hai-Hong Huang; Chao Cheng; Li-Li Guo; Wan-Sheng Zou; Yan-Ju Lei; Wei-Qi Kuang; Bo-Lan Zhou; Pin-Hong Yang; Chao-Yun Li (Fishes, 2025)
This study aimed to induce a shift in a bacterial community by adding substrate into a biofloc system to characterize this shift and estimate its benefits in improving water quality and aquatic animal growth. We compared the bacterial communities between two biofloc systems, either with (sB treatment) or without (nB treatment) the addition of substrate (elastic solid packing filler), and we also analyzed the effects of the shift on the water quality and growth performance of shrimp (Litopenaeus vannamei). Beta diversity analysis indicated that the bacterial communities in the two treatments were significantly different (Jaccard index 0.94 ± 0.01, pseudo-F = 3.96, p = 0.001). The addition of substrate showed significant positive effects on bacterial alpha diversity indices (Shannon, Heip, Pielou, and Simpson; p

Analysis of insertion/deletion variation of litter size in Guizhou black goat - Yang Yang; Yan Pin Zhao; Yong Han (Tropical Animal Health and Production, 2025)

Seismic evidence for magmatism-driven mud volcanism in the northern continental margin of the South China Sea - Junhui Yu; Pin Yan; Yanlin Wang; Guangjian Zhong; Changliang Chen (Marine and Petroleum Geology, 2025)

Complement factor D of Paralichthys olivaceus in serum enhances C3 deposition to activate complement against bacterial infection - Heng Liu; Xiao-yan Jin; Xue-pin Han; Yin Liu; Feng Zhang; Mo-fei Li (Fish & Shellfish Immunology, 2025)

Electroactive biofilm enhances synergistic degradation of sulfamethoxazole and roxarsone in actual livestock wastewater: extracellular electron transfer drives metabolic network remodeling - Pin Peng; Xinyu Yan; Lixiang Chen; Xiang Li; Huiying Yang; Yijing Miao; Feng Zhao (Environmental Research, 2025)

Local collaboration between oxygen vacancy, palladium and platinum trimer triggers exceptional performance in the alkaline fuel cell - Dinesh Bhalothia; Che Yan; Yawei Wu; Jui-Cheng Kao; Yu-Chieh Lo; Haolin Li; Nozomu Hiraoka; Hirofumi Ishii; Yen-Fa Liao; Sheng Dai; Chen-Hao Wang; Alice Hu; et al. (Chemical Engineering Journal, 2025)

Innovative municipal sludge dewatering: High efficiency and high-dryness through the synergistic effect of MoS2 piezoelectric catalysis and electro-dewatering - Binqi Rao; Yulin Li; Zhuo Zeng; Yin Duan; Yan Zhang; Fang Zhou; Weilun Ren; Pin Zhou; Xilong Lu; Quanfa Zhou; Peng Xu (Journal of Environmental Management, 2025)

Variations in the leaf economics spectrum, anatomical, ultrastructural, and stomatal traits of five tree species in the urban-rural air pollution environment - Xiangru Yan; Pin Li; Xianjie Wu; Jiahui Wang; Zejin Wang; Jingliang Xu; Xiaofan Hou; Dayong Fan; Zhengbing Yan; Enzai Du (Journal of Environmental Sciences, 2025)

Effect of layered grinding on the distribution and binding forms of protein and polyphenols in highland barley bran - Muyan Ma; Feng Liang; Wenju Zhou; Pin Ma; Chengjun Ji; Yan Du; Zhaoxin Tu; Li Wang; Xinxia Zhang; Ting Li; Juan Li (Food Bioscience, 2025)

Multi-hazard fragility analysis of cross-sea cable-stayed bridges cable bent tower under seismic-wind combined action - Yan Liang; Yu-zhen Kong; Li Yan; Zheng-hao Zhao; Pin-wu Guan (Soil Dynamics and Earthquake Engineering, 2025)

Upregulation of circRNA_0002286 protects against brain ischemia/reperfusion injury after remote ischemic postconditioning via microRNA-124-3p/VLCAD axis - Chun-Yan Li; Wei Ma; Jin-Wei Yang; Wei Liu; Kuang-Pin Liu; Xiao-Hua Weng; Shou-Rui Niu; Shen Li; Jian-Hui Guo; Li-Yan Li (Journal of Molecular Histology, 2025)

The mafic–ultramafic roots of a magmatic arc from the East Kunlun Orogen, NW China - Zhi-Xiong Zhao; Guo-Chen Dong; M. Santosh; Di-Cheng Zhu; Hui-Lei Kong; Shu-Jun Lü; Pin-Yan Zhong (Gondwana Research, 2025)

Insights into the efficient activation of peracetic acid by Fe/Co−NBC for florfenicol degradation: Performance, mechanism, and toxicity evaluation - Haitian Song; Yan Qin; Yajie Qian; Xiaoqian Chen; Pin Gao (Journal of Environmental Chemical Engineering, 2025)

One-step controllable synthesis of N-doped porous carbon derived from ZIF-8 for efficient capacitive deionization - Pin Hou; Jiaqi Yan; Xiaoyu Yang; Ridha Djellabi; Xinrui Ge; Xinyu Sun; Jianli Jia; Jianbing Wang (Journal of Environmental Chemical Engineering, 2025)

Facile synthesis of trimetallic compounds based on cobalt and nickel with ammonium fluoride-based complex for energy storage applications - Tsai-Mu Cheng; Pei-Chen Kuo; Yi-Chun Lai; Pin-Yan Lee; Chutima Kongvarhodom; Muhammad Saukani; Sibidou Yougbaré; Hung-Ming Chen; Kuo-Chuan Ho; Lu-Yin Lin (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “N-doped carbon dots/g-C3N4 photoexcitation simultaneously enhanced the microbial degradation of nitrate and oxytetracycline in a low C/N ratio aquaculture wastewater” [Chem. Eng. J. 491 (2024) 151763] - Pin Peng; Lixiang Chen; Xinyu Yan; Rui Bai; Bob Adyari; Xudong Zhou; Feng Zhao (Chemical Engineering Journal, 2025)

Early diagenesis of coral rubble on the high-energy platform of Ximen Reef in the southern South China Sea - Shengnan Zhou; Qi Shi; Hongqiang Yang; Shichen Tao; Xiyang Zhang; Hongqiang Yan; Zhiwei Hou; Ji Yang; Wenlong Jing; Pin Yan (Marine Geology, 2025)

Fault materials and creep characteristics in mudstone areas: A case study of Chegualin Fault in southwestern Taiwan - Pin-Hao Chen; Yen-Hua Chen; Ming-Chih Hsieh; Yan-Wei Huang; Chien-Che Huang; Wei-Teh Jiang; Jey-Jau Lee; Yao-Chang Lee; Hwo-Shuenn Sheu (Engineering Geology, 2025)

Morphology, phylogeny, and toxicity of three Gambierdiscus species from the South China Sea, including a coral-killing bloom of G. carpenteri in reef tanks - Zhaohe Luo; Xiangyuan Lin; Xiaowan Liu; Kieng Soon Hii; Haiyan Li; Yan Li; Xinya Xu; Jiaguang Xiao; Hala F. Mohamed; Xinqing Zheng; Li Zhang; Po Teen Lim; et al. (Marine Environmental Research, 2025)

A “two birds one stone” strategy for self-healing marine coatings with antifouling and anticorrosion properties - Yong-Yin Cui; Tian-Cheng Chen; Jia-Ming Zhai; Ying Liu; Ye-Pin Gu; Hui-Jing Li; Yan-Chao Wu (Chemical Engineering Journal, 2025)

Unlocking anaerobic digestion potential via extracellular electron transfer by exogenous materials: Current status and perspectives - Xinyu Yan; Pin Peng; Xiang Li; Xudong Zhou; Lixiang Chen; Feng Zhao (Bioresource Technology, 2025)

Sedimentation-controlled double BSRs and implications for paleo hydrate dissociation in the Shenhu area, south China sea - Wei Deng; Pin Yan; Zenggui Kuang; Jinqiang Liang; Miaomiao Meng; Lei Lu (Marine and Petroleum Geology, 2024)

Enhancing degradation of antibiotic-combined pollutants by a hybrid system containing advanced oxidation and microbial treatment, a review - Pin Peng; Xinyu Yan; Xudong Zhou; Lixiang Chen; Xiang Li; Yijing Miao; Feng Zhao (Journal of Hazardous Materials, 2024)

Effects of polypropylene microplastics on digestion performance, microbial community, and antibiotic resistance during microbial anaerobic digestion - Yu Xiao; Yan Qin; Xiaoying Jiang; Pin Gao (Bioresource Technology, 2024)

MicroRNA dynamics in irisin-mediated signaling pathways within adipose tissue - Ming-Yun Ho; Kai-Pin Chiu; Ming-Lung Tsai; Jih-Kai Yeh; Yi-Chun Huang; Yan-Rong Li; Horng-Dar Wang; I-Chang Hsieh; Ming-Shien Wen; Chao-Yung Wang (Journal of Biosciences, 2024)

Detection of a mud volcano in the Weitan Banks area of the northern South China Sea - Wei Luo; Pin Yan; Yanlin Wang; Junhui Yu; Qionghua Wan; Zhenbo Zhang; Tao Xue (Journal of Oceanology and Limnology, 2024)

Targeted delivery of food functional ingredients in precise nutrition: design strategy and application of nutritional intervention - Xu Wang; Guohua Shi; Sufang Fan; Junmei Ma; Yonghuan Yan; Mengtian Wang; Xiaozhi Tang; Pin Lv; Yan Zhang (Critical Reviews in Food Science and Nutrition, 2024)

Incorporation of atomic Fe-oxide triggers a quantum leap in the CO2 methanation performance of Ni-hydroxide - Amisha Beniwal; Dinesh Bhalothia; Yin-Rong Chen; Jui-Cheng Kao; Che Yan; Nozomu Hiraoka; Hirofumi Ishii; Mingxing Cheng; Yu-Chieh Lo; Xin Tu; Yun-Wei Chiang; Chun-Hong Kuo; et al. (Chemical Engineering Journal, 2024)

N-doped carbon dots/g-C3N4 photoexcitation simultaneously enhanced the microbial degradation of nitrate and oxytetracycline in a low C/N ratio aquaculture wastewater - Pin Peng; Lixiang Chen.; Xinyu Yan; Rui Bai; Bob Adyari; Xudong Zhou; Feng Zhao (Chemical Engineering Journal, 2024)

Fulvic acid-mediated efficient anaerobic digestion for kitchen wastewater: Electrochemical and biochemical mechanisms - Xinyu Yan; Pin Peng; Xudong Zhou; Xiang Li; Lixiang Chen; Feng Zhao (Water Research, 2024)

1300-m-High gas plume from pockmarks in the north Nansha waters, South China sea - Yanlin Wang; Guanghong Tu; Junhui Yu; Pin Yan; Jinfeng Ma; Zhuangcai Tian; Changliang Chen (Marine and Petroleum Geology, 2024)

Co-pyrolysis of sewage sludge and phosphate tailings: Synergistically enhancing heavy metal immobilization and phosphorus availability - Ya Xiao; Tinggui Yan; Pin Yao; Weixue Xiang; Yunqi Wu; Jiang Li (Waste Management, 2024)

Unstable geomorphologic fabric impacted by excess magmas and propagating rifts in the central West Philippine Basin - Weidong Luo; Pin Yan; Gaowen He; Yufang Tan; Ruiying Ye; Hongjun Chen; Zhen Lin; Houjin Wang; Minghui Zuo; Changliang Chen; Junhui Yu; Yanlin Wang (Geomorphology, 2024)

CFD-DEM-based evaluation of main-channel sediment transport processes subject to supplement from a steep tributary - Yi-Pin Nie; Xie-Kang Wang; Xu-Feng Yan (Engineering Geology, 2024)

Endowing polymeric carbon nitride photocatalyst with CO2 activation sites by anchoring atomic cobalt cluster - Yaru Shang; Yijie Hou; Xun Cao; Hengjie Liu; Xiaoli Jin; Jiawei Liu; Chunshuang Yan; Yumin Qian; Li Song; Zeming Qi; Pin Song; Yansong Zhou; et al. (Chemical Engineering Journal, 2024)

Resource recovery of high value-added products from wastewater: Current status and prospects - Zihan Wei; Yan Qin; Xiang Li; Pin Gao (Bioresource Technology, 2024)

Exposure to pesticides and risk of colorectal cancer: A systematic review and meta-analysis - Pin-Peng Xie; Zhi-Qiang Zong; Jian-Chao Qiao; Zhuo-Yan Li; Cheng-Yang Hu (Environmental Pollution, 2024)

Exposure to pentachlorophenol destructs the symbiotic relationship between zooxanthellae and host and induces pathema in coral Porites lutea - Yuanyuan Zhang; Lan Luo; Pin Gan; Xuan Chen; Xiaoli Li; Yan Pang; Xiaopeng Yu; Kefu Yu (Science of The Total Environment, 2024)

Dual role of birnessite on the modulation of acid production and reinforcement of interspecific electron transfer in anaerobic digestion - Xinyu Yan; Lixiang Chen; Pin Peng; Fan Yang; Liping Dai; Han Zhang; Feng Zhao (Science of The Total Environment, 2024)

Subsurface structures and nature of seafloor mounds in the northern South China Sea margin: Implications for Mesozoic hydrocarbon exploration - Junhui Yu; Pin Yan; Yanlin Wang; Guangjian Zhong; Changliang Chen (Geomorphology, 2024)

Efficient degradation of fluoroquinolone antibiotics in the landfill leachate by sludge biochar activated peracetic acid: Radical vs non-radical process - Zilin Zhou; Yan Yang; Gang Xue; Yang Yu; Jiabin Chen; Pin Gao; Yajie Qian (Chemical Engineering Journal, 2024)

Manipulation of crystallization nucleation and thermal degradation of PLA films by multi-morphologies CNC-ZnO nanoparticles - Ya-Fang Yan; Xiao-Bo Liang; Yan-Long Feng; Lin-Fang Shi; Rui-Pin Chen; Jian-Zhong Guo; Ying Guan (Carbohydrate Polymers, 2023)

Metal ion assistant transformation strategy to synthesize catechol-based metal–organic frameworks from Ti3C2T precursors - Weikang Wang; Yan Bai; Pin Yang; Shuai Yuan; Feiyang Li; Weiwei Zhao; Beibei Jin; Xuan Zhang; Shujuan Liu; Daqiang Yuan; Qiang Zhao (Science Bulletin, 2023)

Performance and degradation pathway of florfenicol antibiotic by nitrogen-doped biochar supported zero-valent iron and zero-valent copper: A combined experimental and DFT study - Zheng Tang; Yifan Kong; Yan Qin; Xiaoqian Chen; Min Liu; Lu Shen; Yanming Kang; Pin Gao (Journal of Hazardous Materials, 2023)

Fluid migration patterns in shallow horizontal sand bodies pierced by vertical gas seepage in the Qiongdongnan Basin, South China Sea - Deng Wei; Liang Jinqiang; Yang Zhen; Kuang Zenggui; Yan Pin; Meng Miaomiao; Zhang Zijian (Journal of Asian Earth Sciences, 2023)

Genesis of ferromanganese nodules associated with mud volcanoes in the southeastern Dongsha waters of the northern South China Sea: Implications for regional deep Mesozoic hydrocarbon prospects - Yunfan Zhang; Pengchun Li; Yongbin Jin; Xingjian Liu; Yanlin Wang; Pin Yan; Guangjian Zhong; Yunying Zhang (Marine and Petroleum Geology, 2023)

A novel type of Brassica napus with higher stearic acid in seeds developed through genome editing of BnaSAD2 family - Huibin Huang; Sunny Ahmar; Rana Abdul Samad; Pin Qin; Tong Yan; Qin Zhao; Kabin Xie; Chunyu Zhang; Chuchuan Fan; Yongming Zhou (Theoretical and Applied Genetics, 2023)

Highly-specific aptamer targeting SARS-CoV-2 S1 protein screened on an automatic integrated microfluidic system for COVID-19 diagnosis - Hung-Bin Wu; Chih-Hung Wang; Yi-Da Chung; Yan-Shen Shan; Ying-Jun Lin; Huey-Pin Tsai; Gwo-Bin Lee (Analytica Chimica Acta, 2023)

Predicting the acoustic characteristics of seafloor sediments containing cold spring carbonate rocks - Yuhang Tian; Lei Wu; Dapeng Zou; Zhong Chen; Yongjun Jiang; Pin Yan; Chaoyan Fan (Frontiers in Marine Science, 2023)
The acoustic and physical properties of two valuable marine cold spring carbonate rock samples gathered from the Chaoshan Depression in the South China Sea were measured. The Wyllie time-average equation was applied to analyze the measured sound speeds and their trend under different porosities, and the sound speeds of marine cold spring carbonate rocks were found to be consistent with those of terrestrial carbonate rocks. The Voigt model, Reuss model, and Voigt-Reuss-Hill model were used to predict the characteristics of the sound speed for four states of seafloor sediments containing cold spring carbonate mineral particles or rocks. For these four states of marine cold spring carbonate mineral particles existing on or in seafloor sediments, the sound speed and reflection coefficient of a mixture of seafloor surface sediments containing cold spring carbonate mineral particles or rocks decrease with an increase in the volume ratio of the seafloor sediment. This method for predicting the reflection coefficient provides evidence to explain the high and low reflection coefficients observed in Chirp sub-bottom profiles of cold spring seepage areas.

Estimation of Gas Hydrate Saturation Regarding the Hydrate Morphology in Hydrate-Bearing Sands in the Qiongdongnan Basin, South China Sea - Deng Wei; Liang Jinqiang; Kuang Zenggui; Xie Yingfeng; Yan Pin (Pure and Applied Geophysics, 2023)

Effects of Bacillus strain added as initial indigenous species into the biofloc system rearing Litopenaeus vannamei juveniles on biofloc preformation, water quality and shrimp growth - Hai-Hong Huang; Chao-Yun Li; Yan-Ju Lei; Bo-Lan Zhou; Wei-Qi Kuang; Wan-Sheng Zou; Pin-Hong Yang (Aquaculture, 2023)

Outcomes between endoscopic-assisted minimally invasive surgery and conventional craniotomy in spontaneous intracerebral hemorrhage - Yi-Ying Hsieh; Bo-An Chen; Kuan-Hao Fu; Yi-Hsien Kuo; Ying-Yun Chen; Jiun-Lin Yan; Pin-Yuan Chen (Neurophysiology, 2023)

Origin of a giant fuzzy reflection zone and its implication for natural gas exploration in the southwestern Qiongdongnan Basin of the South China Sea - Junhui Yu; Pin Yan; Yanlin Wang; Yan Qiu; Guanghong Tu; Changliang Chen (Journal of Oceanology and Limnology, 2023)

Discovery of pockmarks in the Zengmu Basin, southern South China Sea and the implication - Yanlin Wang; Guanghong Tu; Junhui Yu; Pin Yan; Yongbin Jin; Changliang Chen; Jie Liu (Journal of Oceanology and Limnology, 2023)

Blue carbon science, management and policy across a tropical urban landscape - Daniel A. Friess; Yasmine M. Gatt; Tze Kwan Fung; Jahson B. Alemu; Natasha Bhatia; Rebecca Case; Siew Chin Chua; Danwei Huang; Valerie Kwan; Kiah Eng Lim; Yudhishthra Nathan; Yan Xiang Ow; et al. (Landscape and Urban Planning, 2023)

Thiobacillus spp. and Anaeromyxobacter spp. mediate arsenite oxidation-dependent biological nitrogen fixation in two contrasting types of arsenic-contaminated soils - Yongbin Li; Lifang Guo; Rui Yang; Zhaohui Yang; Haihan Zhang; Qiqian Li; Zhiguo Cao; Xin Zhang; Pin Gao; Wenlong Gao; Geng Yan; Duanyi Huang; et al. (Journal of Hazardous Materials, 2023)

Geophysical evidence for a serpentine mud volcano in the relict slow-spreading center of the South China Sea - Yanlin Wang; Pin Yan; Junhui Yu; Guanghong Tu; Jun Wang; Yan Qiu; Changliang Chen (Tectonophysics, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Geomorphic development of an unvegetated shingle cay on the Ximen Reef in the southern South China Sea - Shengnan Zhou; Qi Shi; Hongqiang Yang; Lirong Wang; Xiyang Zhang; Xiaoju Liu; Fei Tan; Pin Yan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

The seismic and rock-physics evidences of the different migration efficiency between different types of gas chimneys - Wei Deng; Kuang Zenggui; Liang Jinqiang; Yan Pin; Jingan Lu; Miaomiao Meng (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Analyzing spatial variance of urban waterlogging disaster at multiple scales based on a hydrological and hydrodynamic model - Luoyang Wang; Yao Li; Hao Hou; Yan Chen; Jinjin Fan; Pin Wang; Tangao Hu (Natural Hazards, 2022)

Correction to: LncRNA GATA3‑AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR‑361/ARRB2 axis - Yu‑xi Liu; Shuo Yuan; Xiao‑jing Liu; Yan‑xi Huang; Pin Qiu; Jie Gao; Gao‑pi Deng (Journal of Molecular Medicine, 2022)

Correction to: LncRNA GATA3‑AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR‑361/ARRB2 axis - Yu‑xi Liu; Shuo Yuan; Xiao‑jing Liu; Yan‑xi Huang; Pin Qiu; Jie Gao; Gao‑pi Deng (Journal of Molecular Medicine, 2022)

LncRNA GATA3-AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR-361/ARRB2 axis - Yu-xi Liu; Shuo Yuan; Xiao-jing Liu; Yan-xi Huang; Pin Qiu; Jie Gao; Gao-pi Deng (Journal of Molecular Medicine, 2022)

Effect of gradation variation on particle transport process in a generalized flash flood gully via CFD-DEM method - Yi-pin Nie; Ling Lan; Xu-feng Yan; Xie-kang Wang (Acta Geophysica, 2022)

Habitat Adaptation Mediates the Influence of Leaf Traits on Canopy Productivity: Evidence from a Tropical Freshwater Swamp Forest - Weng Ngai Lam; Pin Jia Chan; Ying Ying Ting; Hong Jhun Sim; Jun Jie Lian; Rie Chong; Nur Estya Rahman; Lorraine Wen Ai Tan; Qian Yi Ho; Zhongyu Chiam; Srishti Arora; Hao Ran Lai; et al. (Ecosystems, 2022)

An Energy-Saving Position Control Strategy for Deep-Sea Valve-Controlled Hydraulic Cylinder Systems - Jia-Bin Wu; Li Li; Yong-Kang Yan; Pin-Jian Wang; Wei Wei (Journal of Marine Science and Engineering, 2022)
The valve-controlled hydraulic cylinder system (VCHCS) is commonly utilized in the underwater manipulator, which is the most important tool for subsea tasks. Hydraulic oil viscosity is very sensitive to pressure. Therefore, when working at different depths under different ambient pressures in the sea, the hydraulic oil viscosity and the pipeline pressure loss in the deep-sea VCHCS vary greatly, which seriously affects the energy efficiency of the system. In addition, the control accuracy of the deep-sea VCHCS is also influenced by changes in the hydraulic oil viscosity and the pipeline pressure loss. In order to realize energy-saving control, this research introduces a proportional relief valve and develops a variable pump pressure control strategy. At the same time, a variable gain proportional-integral-derivative (PID) algorithm is designed to achieve precise control. A co-simulation model of the deep-sea VCHCS is then established, and many simulation analyses are carried out. Compared with traditional PID control with a constant pump pressure, the proposed method presents advantages such as lower energy consumption, better control accuracy, better resistance to load impact, and accuracy consistency under different working depths. Among them, when working at 11 km depth in the sea, the proposed method is capable of saving energy by 36.5% for the multi-step movement, by 30% for the harmonic movement, and by 47% for the complex movement. The present work in this research provides a solution that can realize energy saving and precise control of the deep-sea VCHCS at the same time in the wide span of depth in the sea.

Alteribacter salitolerans sp. nov., isolated from a saline-alkaline soil - Shuang Wang; Lei Sun; Manik Prabhu Narsing Rao; Guo-Hong Liu; Pin-Jiao Jin; Zhou-Yan Dong; Zheng-Han Lian; Xiao-Yu Hao; Ming-Yi Zhang; Wen-Jun Li (Archives of Microbiology, 2022)

Substrate damage and recovery after giant clam shell mining at remote coral reefs in the southern South China Sea - Shengnan Zhou; Qi Shi; Hongqiang Yang; Xiyang Zhang; Xiaoju Liu; Fei Tan; Pin Yan (Journal of Geographical Sciences, 2021)

Long noncoding RNA SNHG1 protects brain microvascular endothelial cells against oxygen–glucose deprivation/reoxygenation-induced injury by sponging miR-298 and upregulating SIK1 expression - Xinyu Zhou; Bingchao Xu; Yan Gu; Niu Ji; Pin Meng; Lingdan Dong (Biotechnology Letters, 2021)

The Roles of Epinephelus coioides miR-122 in SGIV Infection and Replication - Hong-Yan Sun; Yu-Ling Su; Pin-Hong Li; Jia-Yang He; He-Jia Chen; Gang Wang; Shao-Wen Wang; Xiao-Hong Huang; You-Hua Huang; Qi-Wei Qin (Marine Biotechnology, 2021)
In mammals, mature miR-122 is 22 nucleotides long and can be involved in regulating a variety of physiological and biological pathways. In this study, the expression profile and effects of grouper Epinephelus coioides miR-122 response to Singapore grouper iridovirus (SGIV) infection were investigated. The sequences of mature microRNAs (miRNAs) from different organisms are highly conserved, and miR-122 from E. coioides exhibits high similarity to that from mammals and other fish. The expression of miR-122 was up-regulated during SGIV infection. Up-regulation of miR-122 could significantly enhance the cytopathic effects (CPE) induced by SGIV, the transcription levels of viral genes (MCP, VP19, LITAF and ICP18), and viral replication; reduce the expression of inflammatory factors (TNF-a, IL-6, and IL-8), and the activity of AP-1 and NF-κB, and miR-122 can bind the target gene p38α MAPK to regulate the SGIV-induced cell apoptosis and the protease activity of caspase-3. The results indicated that SGIV infection can up-regulate the expression of E. coioides miR-122, and up-regulation of miR-122 can affect the activation of inflammatory factors, the activity of AP-1 and NF-κB, and cell apoptosis to regulate viral replication and proliferation.

Hydroxychavicol, a polyphenol from Piper betle leaf extract, induces cell cycle arrest and apoptosis in TP53-resistant HT-29 colon cancer cells - Aiysvariyah Rajedadram; Kar Yong Pin; Sui Kiong Ling; See Wan Yan; Mee Lee Looi (Journal of Zhejiang University-SCIENCE B, 2021)

Advances in intervention methods and brain protection mechanisms of in situ and remote ischemic postconditioning - Chun-Yan Li; Wei Ma; Kuang-Pin Liu; Jin-Wei Yang; Xian-Bin Wang; Zhen Wu; Tong Zhang; Jia-Wei Wang; Wei Liu; Jie Liu; Yu Liang; Xing-Kui Zhang; et al. (Metabolic Brain Disease, 2021)

Flavobacterium ajazii sp. nov., Isolated from Seaweed of Gouqi Island, China - Ishrat Khan; Sanjit Chandra Debnath; Cen Yan; Can Chen; Yan Xu; Wen-Jie Wang; Yu-Chao Yu; Dao-Qiong Zheng; Jin-Zhong Xu; Pin-Mei Wang (Current Microbiology, 2020)

Preliminary studies of hair follicle regeneration by injections of epidermal stem cells and dermal papilla cells into nude mice - Mingsheng Zhang; Yan Ye; Pin Zhao; Liming Bai; Xinping Li (Cell and Tissue Banking, 2020)
The ultimate goal of organ regenerative therapy is to reproduce fully functional organs to replace which have been damaged as a result of diseases or injury. Although several studies claimed that using different types of cells in some animal models promote hair follicles regeneration, more researches can be done to develop a sufficient and efficient protocol to induce hair generation from different animal models. In this study, we investigated the therapeutic potentials for hair follicle formation by injecting a mixture of epidermal stem cells and dermal papilla cells. Those cells were isolated and culture-expanded. Then we randomly allocated 8 nude mice into two groups. The experiment group received an injection of a mixture that containing of epidermal stem cells and dermal papilla cells. The control group received injection of keratinocyte serum-free medium. The hair follicles regeneration was observed and the injection area was harvested for HE staining. 14 day later, the regenerated hair shafts were observed and HE staining indicated that the newly hair follicle formed the correct structures in experiment group. Furthermore, the mixture injection induced a regular and multilayered stratified epidermis and the epidermis contained of hair follicle-likes structures. Our data showed that injection of a mixture of epidermal stem cells and dermal papilla cells could induce hair follicles regeneration and well-ordered epidermis formation. This study emphasized that the rearrangement of the interactions during seed cells and the niches of the seed cells is essential and necessary for tissue-engineered construct success.

Therapeutic value of nerve growth factor in promoting neural stem cell survival and differentiation and protecting against neuronal hearing loss - Zhao Han; Cong-Pin Wang; Ning Cong; Yu-Yan Gu; Rui Ma; Fang-Lu Chi (Molecular and Cellular Biochemistry, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Deep-Water Sedimentary Characteristics and Response in the Reed Area of the Southern South China Sea - Zheng Hong-Bo; Yan Pin; Yan-Lin Wang; Yu-Qing Xing (Marine Georesources & Geotechnology, 2016)

An AhR-Luciferase Adenovirus Infection System for Rapid Screening of Dioxins in Soils - Cherng-Gueih Shy; How-Ran Chao; Ding-Yan Lin; Yan-You Gou; Chun-Yu Chuang; Kuo Pin Chuang; Chih-Cheng Chen; Yung-Chun Hsiao; Fu-An Chen (Bulletin of Environmental Contamination and Toxicology, 2016)

A New Schiff Base Chemodosimeter for Fluorescent Imaging of Ferric Ions in Living Cells - Yan-Zi Chen; Yeshwant Ramchandra Bhorge; Albert J. Pape; Rupesh D. Divate; Yun-Chin Chung; Yao-Pin Yen (Journal of Fluorescence, 2015)

Application of AVO analysis to gas hydrates identification in the northern slope of the South China Sea - Rui Yang; Pin Yan; Nengyou Wu; Zhibin Sha; Jinqiang Liang (Acta Geophysica, 2014)

Fluid inclusion and H–O–C isotope geochemistry of the Yaochong porphyry Mo deposit in Dabie Shan, China: a case study of porphyry systems in continental collision orogens - Pin Wang; Yan-Jing Chen; Bin Fu; Yong-Fei Yang; Mei Mi; Zhong-Lie Li (International Journal of Earth Sciences, 2014)

Deep-Water Bottom Current Research in the Northern South China Sea - Zheng Hong-Bo; Yan Pin (Marine Georesources & Geotechnology, 2012)

Structural Characterization of Extracellular Polysaccharides Produced by the Marine Fungus Epicoccum nigrum JJY-40 and Their Antioxidant Activities - Hai-Hong Sun; Wen-Jun Mao; Jie-Ying Jiao; Jia-Chao Xu; Hong-Yan Li; Yin Chen; Xiao-Hui Qi; Yan-Li Chen; Jian Xu; Chun-Qi Zhao; Yu-Jiao Hou; Yu-Pin Yang (Marine Biotechnology, 2011)

Immunohistochemical Detection of Apoptotic Proteins, p53/Bax and JNK/FasL Cascade, in the Lung of Rats Exposed to Cigarette Smoke - Cheng-Hsun Wu; Hui-Hsuan Lin; Fu-Pin Yan; Cheng-Hua Wu; Chau-Jong Wang (Archives of Toxicology, 2006)